Modeling Emergent Variables to Assess the Adoption of Activity-Based Costing in Tanzania: The Application of Confirmatory Composite Analysis: Composite Model and ABC Adoption in Tanzania - Molela, Godfrey; Kasoga, Pendo; Ismail, Ismail (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The applications of composite models in explaining the adoption of innovations continue to gain widespread recognition in contemporary research. This study examines the role of a composite model comprising innovation attributes, contingency factors, and isomorphic pressures in explaining the adoption of activity-based costing (ABC) in Tanzania. The examined causal relationship between the model and ABC adoption is subject to mediation by behavioral preferences. More importantly, this study evaluates the overall fit of the model based on confirmatory composite analysis (CCA) as a prerequisite for path analysis. Design/methodology/approach: Data were collected from 188 manufacturing and service companies in Tanzania using a cross-sectional survey design. As part of CCA, the study employed principal component analysis (PCA) to form the three emergent variables namely innovation attributes, contingency factors and isomorphic pressures. It is these variables that were merged together to form the composite model whose influence on ABC adoption was analyzed based on partial least squares structural equation modeling (PLS-SEM). Research Findings: It was found out that, it is only normative beliefs that positively mediated the causal - relationship between the composite model and ABC adoption. This suggests that, the combined influences of internal and external factors defined by innovation attributes, contingency factors and isomorphic pressures towards ABC adoption is mediated by the belief that manufacturing and service companies should adopt the system. On the other hand, the perceptions of the system’s usefulness and ease to use do not play role in explaining the combined influences of factors on ABC adoption. Theoretical Contribution/Originality: The findings are paramount in creating the reference base for future studies as there were no previous studies of similar nature conducted to assess the impact of the composite model on ABC adoption. Keyword: Composite model, Innovation attributes, Contingency factors, Isomorphic pressures, Activity-based costing, Confirmatory composite analysis